Bird's eye view of the city of Paris, Bourbon County, Kentucky 1870. - Ruger, A. (1870)
AACR2: 100; 651/1; Indexed for points of interest.; Perspective map not drawn to scale.; Vault; "Looking south east."; Available also through the Library of Congress Web site as a raster image.; LC Panoramic maps (2nd ed.), 239